Influence of the original electrogenic bacteria on the performance of oily sludge Microbial Fuel Cells. (November 2022) - Guo, Haiying; Huang, Chunfeng; Geng, Xiaoheng; Jia, Xinlei; Huo, Hongjun; Yue, Weimin
Abstract: The species and power generation performance of the original electrogenic bacteria determine the pollution control and power generation performance of the microbial fuel cells. However, there are few studies on the effect of original electrogenic bacteria on the performance of oily sludge microbial fuel cells. More importantly, the electron transfer mode of original electrogenic bacterial was explored. The results of this study showed that the addition of electrogenic bacteria No. 2 and No. 3 alone can improve the power generation performance of oily sludge microbial fuel cell, and the addition of electrogenic bacteria No. 2 has a more obvious improvement effect. The maximum output voltage, power density and crude oil removal rate are 384.90 mV, 1277.90 mW ⋅ m −3 and 56.51%, respectively. And it also shorten the degradation time of petroleum hydrocarbons of microbial fuel cell, the half-life (16 d) was shorter than that of the control group microbial fuel cell. There are electron mediators in the secretion of bacteria No. 2, which can assist the electron transfer to the surface of the anode, and the electron transfer method is mainly electronic mediator transfer. The secretion of bacteria No. 3 exist few electronic mediators, and the electron transfer main method is "nanowire"​ transmission or direct contact transmission. The study of the functional bacteria will provide beneficial assistance for the improvement of oil removal and power generation performance of oily sludge microbial fuel cells.